Transactions Costs and Holding Periods for Common Stocks. - Atkins, Allen B; Dyl, Edward A (Journal of Finance, 1997)
Yakov Amihud and Haim Mendelson (1986) and George Constantinides (1986) provide a theoretical basis for the proposition that assets with higher transactions costs are held by investors for longer holding periods, and vice versa. The authors examine average holding periods and bid-ask spreads for Nasdaq stocks from 1983 through 1991 and for New York Stock Exchange (NYSE) stocks from 1975 through 1989 and find strong evidence that, as predicted, the length of investors' holding periods is related to bid-ask spreads. They also find that the relation between holding periods and bid-ask spreads is much stronger on Nasdaq, where spreads are larger, than on the NYSE, where spreads are smaller.